Pattern of hypothyroid cases in Bangladeshi People: A pilot study (Bangladesh Journal of Medical Science, 2013)
Aims: The present study was undertaken to explore the pathological basis of hypothyroidism and it relationship to clino-biochemical features of Bangladeshi patients. Material and Methods: A total number of 47 hypothyroid patients with duration less than two years and had no other comorbid disease were consecutively recruited from BIRDEM Out-patient department. Patients having serum FT4 level 5.01 IU/ml were identified as hypothyroidism. Presence of either anti TG antibody >40 IU/ml or anti TPO antibody > 35 IU/ml or both were defined as autoimmune hypothyroidism. Thyroid gland was examined and classified according to joint criteria of WHO, UNICEF and ICCIDD criteria. Results: Female preponderance was observed in this series though small total number of samples. Familial hypothyroidism was reported in 19% of cases and 8% of patients came from iodine deficient area. Out of 47 cases autoimmune markers were done in 40 and of them 32 (68%) were positive for autoantibodies. Of the positive case 22% were positive for anti TPO antibody and 6% for anti TG antibody; 72% cases both. Drug and radiation were excluded as the cause of hypothyroidism in this series. Family history of hypothyroidism was positive in 22% and 25% autoimmune and non-autoimmune study cases. Of the autoimmune case 44% had age between 30-44 years and among non-autoimmune case 37% were 15-30 years. Eleven of 32 (34%) autoimmune hypothyroid cases presented with irregular menstrual cycle. Out of 47 hypothyroid patients in this study, 36 (77%) had palpable or enlarged thyroid gland. Of the 40 cases autoimmune status evaluated palpable among 25 (78%) autoimmune and 6 (75%) non-autoimmune hypothyroid patients. Conclusions: It is concluded that higher proportion of hypothyroid cases are of antoantibody positive. These subjects have heterogeneous phenotypic presentation. This necessitates that all newly detected hypothyroidism should be screened for autoimmune status with the same importance as given for thyroid hormone level and managed accordingly. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16660 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 405-412